STANDAR OPERASIONAL PROSEDUR (SOP) BERDASARKAN TIPOLOGI SERTIFIKASI KOMPETENSI SUMBER DAYA MANUSIA LEMBAGA KEUANGAN MIKRO SYARI’AH - Sumantri, Bambang Agus (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
Posts in this journal intended as a study and analysis regarding certification of competence standard typology of Human Resources Managers and employees as a form of profesioanalisme Islamic microfinance services management (BMT, BTM, and KJKS).